Tsg101 is recruited by a late domain of the nucleocapsid protein to support budding of Marburg virus-like particles - Dolnik, Olga; Kolesnikova, Larissa; Stevermann, Lea; Becker, Stephan (Journal of virology, 2010)
The nucleoprotein NP of Marburg virus (MARV) is the major component of the viral nucleocapsid, which also consists of the viral proteins VP35, L, and VP30, as well as the viral genome. During virus assembly at the plasma membrane, the nucleocapsids are enwrapped by the major matrix protein VP40 and the viral envelope, which contains the transmembrane glycoprotein GP. Upon recombinant expression, VP40 alone is able to induce the formation and release of virus-like particles (VLPs) that closely resemble the filamentous morphology of MARV particles. Release of these VP40-induced VLPs is partially dependent on the cellular ESCRT machinery, which interacts with a late-domain motif in VP40. Coexpression with NP significantly enhances the budding of VP40-induced VLPs by an unknown mechanism. In the present study we analyzed the impact of late domains present in NP on the release of VLPs. We observed that the ESCRT I protein Tsg101 was recruited by NP into NP-induced inclusions in the perinuclear region. In the presence of VP40, NP was then recruited to VP40-positive membrane clusters and, in turn, recruited Tsg101 via a C-terminal PSAP late-domain motif in NP. This PSAP motif also mediated a dramatically enhanced incorporation of Tsg101 into VLPs, and its deletion significantly diminished the positive effect of NP on the release of VLPs. Taken together, these data indicate that NP enhances budding of VLPs by recruiting Tsg101 to the VP40-positive budding site through a PSAP late-domain motif.